DENV-2 outbreak associated with cosmopolitan genotype emergence in Western Brazilian Amazon - Ribeiro, Jessiane Rodrigues (2024)
The Fundação Rondônia de Amparo ao Desenvolvimento das Ações Científicas e Tecnológicas and the Pesquisa do Estado de Rondônia—FAPERO, as well as the Instituto Nacional de Ciência e Tecnologia de Epidemiologia da Amazônia Ocidental—INCT—EpiAmo they have been important contributors to scientific development in the Amazon region. Collaboration from the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), from whom some authors received financial support (scholarships) during the production of this study, the Instituto de Biologia Molecular do Paraná (IBMP), the Laboratório Central de Saúde Pública de (LACEN/RO), Coordenação de Vigilância em Saúde e Laboratórios de Referência, the Rede de Plataformas Tecnológicas FIOCRUZ RPT09F-FIOCRUZ/RO, Rede Genômica da Fundação Oswaldo; Agência Estadual de Vigilância Sanitária de Rondônia (AGEVISA-RO), and the Secretaria Municipal de Saúde (SEMUSA).